Determining women's sexual self-schemas through advanced computerized text analysis. (August 2015) - Stanton, Amelia M.; Boyd, Ryan L.; Pulverman, Carey S.; Meston, Cindy M.
Abstract: The meaning extraction method (MEM), an advanced computerized text analysis technique, was used to analyze women's sexual self-schemas. Participants ( n = 239) completed open-ended essays about their personal feelings associated with sex and sexuality. These essays were analyzed using the MEM, a procedure designed to extract common themes from natural language. Using the MEM procedure, we extracted seven unique themes germane to sexual self-schemas: family and development, virginity, abuse, relationship, sexual activity, attraction, and existentialism. Each of these themes is comprised of frequently used words across the participants' descriptions of their sexual selves. Significant differences in sexual self-schemas were observed to covary with age, relationship status, and sexual abuse history.